Ambulances are for emergencies: shifting behaviour through a research-informed behaviour change campaign - Kim Borg; David Dumas; Emily Andrew; Karen Smith; Tony Walker; Matthew Haworth; Peter Bragge (Health Research Policy and Systems, 2020)
Abstract Background A major review of Victoria’s ambulance services identified the need to improve public awareness of the role of ambulances as an emergency service. A communications campaign was developed to address this challenge. This research paper expands on an initial evaluation of the campaign by focusing on the long-term behavioural outcomes. Methods The behavioural evaluation involved two types of data collection – administrative data (routine collection from various health services) and survey data (cross-sectional community-wide surveys to measure behavioural intentions). Results Behavioural intentions for accessing two of the targeted non-emergency services increased after the second phase of the campaign commenced. There was also a significant change in the slope of call trends for emergency ambulances. This decrease is also likely attributed to the second phase of the campaign as significant level effects were identified 3 and 9 months after it commenced. Conclusions A long-term campaign developed through evidence review, stakeholder consultation and behavioural theory was successful in reducing the number of daily calls requesting an emergency ambulance in Victoria and in increasing intentions to use alternative services. This research highlights the importance of collaborative intervention design along with the importance of implementing a robust monitoring and evaluation framework.